Innovative Hybrid Compounds Targeting Tuberculosis: Development, Characterization and Bioefficacy analysis of 6-substituted-2-Chloroquinoline-3-Carbaldehyde Hydrazide Ester derivatives (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
This study delves into the biological activity of ester compounds obtained from analogues of 6-substituted-2-chloroquinoline-3-carbaldehyde hydrazide, aiming to exploit the combined antitubercular properties of quinoline and hydrazide to create innovative hybrid compounds. The molecules underwent a meticulous multi-step synthesis process, followed by purification through recrystallization. Methodologies such as 1H NMR, 13C NMR, FTIR and Mass Spectrometry was used to confirm the molecular structures of developed derivatives. SWISSADME, an online tool, was utilized to predict the ADME properties, shedding light on their pharmacokinetic profiles. Evaluation of in vitro antitubercular activity employing the Alamar blue method highlighted compounds 4a and 4f, exhibiting noteworthy efficacy achieving threshold concentrations of 6.25 µg/ml for M. tuberculosis inhibition. These findings suggest the possibility of novel quinoline Scaffold as potential molecule for TB treatment, contributing to ongoing endeavors in TB drug discovery and potentially laying the groundwork to develop effective antitubercular therapies.